1959
DOI: 10.1111/j.1151-2916.1959.tb13574.x
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth Polymorphism and Phase Equilibria in Rare-Earth Oxide-Water Systems

Abstract: A high-water-pressure high-temperature study has been conducted of the systems Y2O3-H2O, Smz03-Hz0, Ndr03-Hz0, and Laz03-H20. The trihydroxides La(OH)3, Nd(OH)r, and Sm(OH)3 are isomorphous, but Y(OH)a does not belong to this group. On the other hand, the oxyhydroxides YOOH, SmOOH, and NdOOH are isomorphous; LaOOH, if it exists, cannot be stable in the presence of water at room temperature. Pressuretemperature curves for the equilibrium between the trihydroxide, oxyhydroxide, and a new hydroxy compound have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
1

Year Published

1961
1961
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(67 citation statements)
references
References 13 publications
5
61
0
1
Order By: Relevance
“…For example, as the cubic and the tetragonal crystal structures are much alike, the dissociation of water molecules on the cubic surface and the formation of Zr±OH, Y±OH and YO(OH) in the cubic lattice are also possible. In the work of Lange et al [2], a thin foil of a composition of 6.6 mol% Y 2 O 3 ±ZrO 2 was annealed for 16 h at 250 C in an environment containing water vapor, a subsequent TEM observation of the foil found that clusters of Y(OH) 3 [14]. But in Lange's experiment, no evidence proved that the Y(OH) 3 crystallites, at least partly, were not formed from the cubic grains.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as the cubic and the tetragonal crystal structures are much alike, the dissociation of water molecules on the cubic surface and the formation of Zr±OH, Y±OH and YO(OH) in the cubic lattice are also possible. In the work of Lange et al [2], a thin foil of a composition of 6.6 mol% Y 2 O 3 ±ZrO 2 was annealed for 16 h at 250 C in an environment containing water vapor, a subsequent TEM observation of the foil found that clusters of Y(OH) 3 [14]. But in Lange's experiment, no evidence proved that the Y(OH) 3 crystallites, at least partly, were not formed from the cubic grains.…”
Section: Introductionmentioning
confidence: 99%
“…Th e hexagonal A type (a=3.831 A, c=5 .999 A) [8], is ge nerally regarded as the stable modification of Nd"203 although th ere has been so me co ntrov ersy regarding the existence and stability of the Band C types [6,7]. Th e melting point of Nd 2 0 3 is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…N eo dymium ses quioxide (Nd 2 0;]) has bee n reported to occ ur in three polymorphi c form s; th e A, B, and C rare earth oxide s tru ct ure types [6,7] . Th e hexagonal A type (a=3.831 A, c=5 .999 A) [8], is ge nerally regarded as the stable modification of Nd"203 although th ere has been so me co ntrov ersy regarding the existence and stability of the Band C types [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…According to the phase diagram of Y 2 O 3 -H 2 O system [18], Y 2 O 3 is not stable under hydrothermal conditions at temperature lower than 550 °C, so that the products of hydrothermal reaction are normally precursors of yttrium oxide rather than oxide itself. The precursors decompose into the oxide through heat treatments.…”
Section: Introductionmentioning
confidence: 99%